The Effect of Profit Growth, Capital Structure, and Accounting Conservatism on Profit Quality - Hasna, Salsabila Nur; Sinarasri, Andwiani (Economics and Business International Conference Proceeding, 2024)
This study intends to analyze the influence of profit growth, capital structure, and accounting conservatism on profit quality in infrastructure sector companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2023. This study uses multiple linear regression analysis as a method. The research sample is 11 infrastructure sector companies using Purposive Sampling. The results of the study partially show that profit growth (X1) has a positive effect on profit quality, capital structure (X2) has a negative effect on profit quality, and accounting conservatism (X3) has a negative effect on profit quality. Meanwhile, simultaneously it shows that profit growth, capital structure, and accounting conservatism affect the quality of profits. Increased profit growth will improve the quality of profits, but an increase in the capital structure of debt and the application of accounting conservatism in the preparation of financial statements will reduce the quality of profits. The company is expected to consider the level of debt it has and conservative behavior in the preparation of financial statements.